Therapeutic potential of purinergic signalling for diseases of the urinary tract - Burnstock, Geoffrey (BJU international, 2011)
What’s known on the subject? and What does the study add? Purinergic signalling, i.e. ATP acting as an extracellular messenger, has been implicated in control of urinary tract function since 1972. For example, it was shown to be a cotransmitter with acetylcholine in parasympathetic control of bladder contraction and purinoceptors on suburothelial sensory nerves mediating both reflex voiding and pain in response to ATP released from urothelial cells during bladder and ureter distension. The most recent studies of purinergic signalling in lower urinary tract pathology includes consideration of the therapeutic potential of purinergic compounds in incontinence, pain, cancer, and in acupuncture, widely used for the treatment of urinary disorders. This review begins with background information about the discovery and conceptual steps contributing to our current knowledge of purinergic signalling. It then deals with several topics concerned with the physiology and pathophysiology of the lower urinary tract, including: the involvement in the voiding reflex of ATP released as a co‐transmitter with acetylcholine from parasympathetic nerves supplying the bladder and ATP released from urothelial cells during bladder distension to initiate the voiding reflex via P2X3 receptors on suburothelial low‐threshold sensory nerve fibres; this latter mechanosensory transduction pathway is also involved via high‐threshold fibres in the initiation of pain. Treatment of prostate and bladder cancer with ATP not only appears to be effective against the primary tumours, but also improves the systemic symptoms associated with advanced malignancy. There is dual control of the tone of blood vessels: constriction by ATP released as a co‐transmitter from sympathetic nerves and vasodilatation via ATP released from endothelial cells during shear stress acting on endothelial P2 receptors to release nitric oxide. A purinergic hypothesis is discussed for the mechanism underlying acupuncture, widely used for the treatment of urinary disorders.